The Role of Ethical Environment in Reducing Escalation of Commitment Bias - Wahyudi, Tertiarto; Yusnaini, Yusnaini; Novriansa, Agil (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
Several empirical studies have shown that decision makers tend to experience an escalation of commitment bias, namely a tendency to continue investment projects that are less profitable, even though there is information of the less profitable project performance and that other available alternative investment opportunities are more profitable in the future. This study aims to improve the manager's decision making behavior model by considering the ethical environment as one of the factors that influence investment project evaluation decisions. More specifically, this study empirically examines the ethical environment as a strategy to reduce the tendency for escalation of commitment behavior. This study uses a laboratory experimental method with a 2 x 2 factorial experimental design between subject with adverse selection (present / absent) and ethical environment (strong / weak). The research sample consisted of 246 undergraduate and postgraduate students in Accounting and Management who acted as investment project managers. Based on ANOVA analysis results, it shows that managers who experience adverse selection conditions tend to continue unfavorable projects (conduct escalation of commitment). In addition, the results of this study also show that the tendency of managers to end investment projects that are not profitable for managers who are in a condition of a strong ethical environment will be greater when they experience adverse selection conditions compared to when they do not experience it.